Negative plant-soil feedbacks disproportionally affect dominant plants, facilitating coexistence in plant communities - Elias P. Goossens; Vanessa Minden; Flor Van Poucke; Harry Olde Venterink (npj Biodiversity, 2023)
Abstract Plant-soil feedbacks (PSFs) are suggested to be major drivers of plant species coexistence and exotic invasions in natural plant communities, where species with more positive PSFs are thought to be more abundant in communities. Most evidence for this comes from mesocosm experiments with single species, but whether the results are transposable to diverse plant communities is mostly not verified and remains debated. We performed a combined monoculture and community experiment to test whether PSFs in monocultures predict PSFs in communities, and to infer the role of PSFs in invasive plant success. We found that (1) PSFs from monocultures were poor predictors for PSFs in plant communities, (2) competitive strength of invasive species did not consistently depend on PSF, and (3) dominant species experienced a significantly stronger negative PSFs than non-dominant species when grown in community. Hence, PSFs of plant species in monocultures seem less predictive for their abundance in plant communities or for invasibility than previously assumed. Nevertheless, PSF—and particularly negative PSF—seems indeed a major driver of plant species coexistence, with a strong species-specific pathogenic effect on dominant plants facilitating the persistence of rare species.